Strategi Coping Perempuan Korban Kekerasan dalam Pacaran di Rifka Annisa Women Crisis Center Yogyakarta - Aziz, Yogi Abdul (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
This article aims to coping strategy have to do by adolescent women become violence of victims in the dating couple and the reason violence of victims to choice for coping strategy. This paper is developed from field research which has to qualitative approach with a case study of the type in the NGOs of Rifka Annisa. In through this method, the data have to collecting with used technic of the interview, observation, and documentation. In this literature studies, the resources have used as well as the informant—the choice of informant used snowball methode—making of choice for 4 (four) people; namely 2 counselors (psychologist and lawyers), and 2 volunteer. The choice of 3 informants in this study, with the reason of the direction in the case violence of victims, become a counselor in the process coping for violence of victims in the dating couple. This paper can be seeing that coping strategy to do by adolescent women on the violence of victims in the dating couple with a demand of social assistance to friends, parent, family, and NGOs of Rifka Annisa. Meanwhile, the reason of underlying victims has used coping strategy, there are avoided from the problem which the accidence, cut relationship from subject victims, selfdetermination for the future, and therapist of reflection in the Rifka Annisa. Coping strategy in the action of behavior are used two approaches, i.e. coping problem-focused coping (PFC) and emotion-focused coping (EFC).